Correlation of serum homocysteine levels and pregnancy outcome: the dilemma continues - Jaiswal, Noopur; Agrawal, Anjoo; Agrawal, Smriti; Das, Vinita; Pandey, Amita; Singh, Rajendra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Hyperhomocysteinemia has been implicated as a risk factor for complications in pregnancy including abortion, preeclampsia and placental abruption. The present study was designed to study the correlation, if any, of Hyperhomocysteinemia with pregnancy outcome. Methods: Pregnant women between 14 to 24 weeks of gestation were included as subjects. Serum homocysteine levels and MTHFR gene (Methylenetetrahydrofolate reductase 677C>T) polymorphism was estimated. The women were followed till delivery and obstetric & neonatal outcomes were noted. Results: A total of 81 women were followed till delivery. Out of these 42 women had an uncomplicated pregnancy and delivery and 39 women had at least one antenatal or perinatal complication. Difference between mean serum homocysteine in both the groups was not statistically significant (p=0.403).No significant difference was found in the occurrence of different genotypes in the 2 groups though women with TT genotype were found to have higher serum homocysteine levels as compared to other genotypes. Conclusions: Though the serum homocysteine levels were higher in the women with pregnancy complications as compared to women without complications but the difference was not statistically significant.